2015
DOI: 10.22201/fesi.20070780.2014.6.2.48590
|View full text |Cite
|
Sign up to set email alerts
|

Validación de la escala Sentido de Coherencia (SOC) 13-item en una muestra Peruana

Abstract: <p>El propósito del estudio fue evaluar las propiedades psicométricas de la escala SOC-13 en una muestra de 448 universitarios peruanos con edades entre 18-29 años. La confiabilidad se calculó con el coeficiente de alfa de cronbach, y se encontró un .80 para toda la escala. La estructura interna del instrumento se evaluó mediante análisis de escalamiento multidimensional y análisis factorial confirmatorio. El análisis factorial confirmatorio se estimó comparando el ajuste de dos modelos propuestos, uno u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
8

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 0 publications
0
5
0
8
Order By: Relevance
“…These results were higher than those from Iranian College students in which the reliability of the personal structure subscale was low [40]. The low internal consistency of the personal structure subscale might be attributed to the number of items (5 items) instead of inadequate reliability as suggested by [39]. The findings indicated that with the exception of two resilience factors, Personal Competence (t = 3.91, p<0.01) and Family Coherence (t = 3.39, p<0.01), (Total RSA, t = 3.91, p < .01), the rest of the RSA factors were insignificant predictors of depression (Social Competence, t = .669 p = n.s.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…These results were higher than those from Iranian College students in which the reliability of the personal structure subscale was low [40]. The low internal consistency of the personal structure subscale might be attributed to the number of items (5 items) instead of inadequate reliability as suggested by [39]. The findings indicated that with the exception of two resilience factors, Personal Competence (t = 3.91, p<0.01) and Family Coherence (t = 3.39, p<0.01), (Total RSA, t = 3.91, p < .01), the rest of the RSA factors were insignificant predictors of depression (Social Competence, t = .669 p = n.s.…”
Section: Discussionmentioning
confidence: 68%
“…In a review of more than 42 different studies in 14 different languages, the SOC was found to have different factor structures concluding that the one-factor structure was the fit and appropriate one. In contrast, Saravia, Iberico, & Yearwood [39] found that that a three factor solution was a better model fit for the Peruvian sample. Nevertheless, certain items did not perform properly and accurately.…”
Section: Sense Of Coherence Scale (Soc)mentioning
confidence: 84%
See 1 more Smart Citation
“…The SOC construct and the SOC-13 scale have been linked to health outcomes in research on most continents, including various cultures, including Western, Asia, and Africa, in diverse samples (Dudek & Koniarek, 2000; Eriksson & Mittelmark, 2017; Erim et al, 2011; Evans & Davis, 2018; Koelen et al, 2017; Stansfeld et al, 2019). However, the SOC scale has been criticized for its inconsistent psychometric properties (Getnet & Alem, 2019; Jakobsson, 2011; Saravia et al, 2014; Sardu et al, 2012). These criticisms have focused on low internal consistency for the subscales and low regression weights for particular items.…”
Section: Discussionmentioning
confidence: 99%
“…Valora las dimensiones comprensibilidad (COMP), manejabilidad (MANEJ) y significatividad (SIGN), (25,26). El resultado permite calcular la puntuación media de cada dimensión y puntuación media global para obtener el SOC, una puntuación global superior a la media indica SOC alto.…”
Section: Materiales Y Métodosunclassified